Порівняльний аналіз систем програмування мікроконтролерів серії STM32 у виробах авіаційного застосування - Vialov, Serhii; Dunai, Andrii (Avìacìjno-kosmìčna tehnìka ì tehnologìâ, 2023)
The subject of the research is the software development environment for STM32 series microcontrollers, which play an important role in the electronic support of modern aviation and are an integral part of the development process of aircraft systems. Goal. The selection of the most current STM32 series microcontroller programming system for aviation products. Tasks. Overview of major popular software development environments for STM32 microcontrollers such as STM32CubeIDE, VisualGDB, IAR Embedded Workbench for ARM, Keil MDK, Arm Development Studio, and Simulink. Various aspects of programming systems are considered, including software development, feature availability, and integration with development tools and environments. Research methods. Carrying out a comparative analysis; separation of the characteristic features of the use of programming environments in avionic devices using the example of JSC "Element". In view of the use of environments in the field of avionics, special attention was paid to certification and reliability using examples of safety standards, verification, and testing tools. The results. It was found that code debugging, memory analysis, code optimization, and other basic functions are inherent to all considered development environments. Distinguishing features inherent in individual programming environments are identified, including microcontroller robot simulation, high performance and compilation speed, open source code, optimization, support from the manufacturer, and a wealth of documentation, including user manuals, code examples, support forums, training courses, webinars, and articles from development companies. Conclusions (scientific and practical novelty). The results of the analysis provide important conclusions regarding the better choice of STM32 microcontroller programming systems in aviation products. The comparisons and analyses made will help software developers choose the most suitable programming system for their specific needs. A conclusion was made about the feasibility of using development environments such as IAR Embedded Workbench for ARM and STM32CubelIDE for developing aviation software based on STM32.